A Model for Bundled Conductors considering a Non-Homogeneous Distribution of the Current through Subconductors - Costa, E. C. M. [UNESP]; Kurokawa, S. [UNESP]; Pissolato, J.; Prado, A. J. [UNESP]; Bovolato, L. F. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
This paper describes an alternative procedure to obtain an equivalent conductor from a bundled conductor, taking into account the distribution of the current in subcondutors of the bundle. Firstly, it is introduced a brief background about the concept of Geometric Mean Radius (GMR) and how this methodology is applied to define an equivalent conductor and its electric parameters. Emphasizing that the classical procedure, using GMR, is limited to premise which the current is equally distributed through subconductors. Afterwards, it is described the development of proposed method and applications for an equivalent conductor obtained from a conventional transmission line bundled conductor and from an equivalent conductor based on a bundle with compressed SF(6) insulation system, where the current is unequally distributed through subconductors.
Keywords: Transmission lines; bundled conductors; frequency-dependent parameters; modal domain; geometric mean radius